Synchronous vibration control for magnetically suspended control moment gyros using optimal notch filter. Issue 7 (1st March 2020) - Peng, Cong; Zhu, Mengting; Liu, Xiaoyue; Chao, Shan; Zhen, Ziyang
Abstract : The synchronous vibration in magnetically suspended control moment gyros is a common problem due to unavoidable rotor mass imbalance. This work proposes an optimal notch filter for suppressing the synchronous vibration force. The synchronous vibration force is firstly modelled, and the preliminary design of phase‐shift notch filter is given to ensure the system stability. Then the optimal phase of notch filter is discussed, and its theoretical expression is given. Finally, simulation results illustrate the superiority of the notch filter with optimal phase, and experimental results verify the effectiveness of optimal notch filter.